Genetic Polymorphisms of the Efflux Transporter Gene ABCB1 and Their Effects on the Anastrozole Response in Iraqi Breast Cancer Patients - Hiba Salah Mahdi; Ahmed Salih Sahib; Hassan Mahmood Mousa Abo Almaali; Karrar Kadhim Mohsin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The ABCB1 gene (ATP-binding cassette) encodes the ABCB1 transporter. Anastrozole is asubstrate for the ABCB1 efflux transporter. The objective of the study was to detect the genetic polymorphismsof this efflux transporter in Iraqi breast cancer patients and their effects on the anastrozole response.Method: Blood samples were taken from breast cancer patients, and a portion of each sample was used forbiochemical analysis (measuring estradiol and cancer antigen 15.3 levels), while the remaining portion wasused for genetic analysis. Genotyping demonstrates that the mutant genotype being the most frequent typefor both C1236T and C3435T SNPs.Results: The result indicated nonsignificant differences in the serum levels of estradiol or cancer antigen15.3 among different genotype groups of the ABCB1 gene.Conclusion: It is concluded that the ABCB1 gene is highly polymorphic in Iraqi women with breast cancer.This study indicated that ABCB1 gene may not affect the response to anastrozole.